Exploring the Mediating Role of Organizational Ambidexterity between Entrepreneurial Orientation and Business Performance in SMEs - Laily, Nur; Mahargiono, Ponco Bambang; Sari, Juwita; Anantamongkolkul, Chidchanok (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study contributes to the academic understanding of how organizational ambidexterity mediates the relationship between entrepreneurial orientation and business performance among SMEs in East Java, Indonesia. Using a quantitative approach, data were gathered from 200 SME respondents through a semi-structured questionnaire. PLS-SEM was employed to analyze both direct and indirect effects. The results reveal that entrepreneurial orientation positively influences both exploration and exploitation dimensions of ambidexterity, which subsequently support improved business performance. The mediation analysis further indicates that ambidexterity plays a pivotal role in translating entrepreneurial posture into performance outcomes. These findings offer practical value for SME leaders by highlighting the importance of balancing short-term operational routines with longer-term adaptive initiatives to remain competitive in a changing business landscape.